PERAN PENYULUHAN DAN HUBUNGANNYA TERHADAP TINGKAT KEBERDAYAAN PETANI SAGU DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Ricardo Bagariang; Rosnita '; Kausar ' (Fakultas Pertanian, Universitas Riau, 2016)
The aim of this research is: 1) To know the counseling had been do that by roler of agriculture farming activities sago in the districts of Tebing Tinggi Timur, 2) Determine the level of empowerment sago farmers in the districts of Tebing Tinggi Timur, 3) Conduct analysis of how much the relationship role of extension to the level of empowerment of sago farmers in the districts of Tebing Tinggi Timur. This research used survey method. Research do in districts of Tebing Tinggi Timur Kepulauan Meranti district starts from April to October 2016. Respondents as many as 60 sago farmers has taken in Purpossive Sampling. The data analysis be used is Scala Likert analysis and Rank Spearman analysis. The result of research shown that: 1) the counselin implementation in districts of Tebing Tinggi Timur less result like hoped of farmer in delivery of material and organized the result of sago farmer, and the role of education in districts of Tebing Tinggi Timur are less “willing category” with score average 2,38. 2) The level of empowerment of sago farmer in districts of Tebing Tinggi Timur in category “quite helpless” with a score average 2,73. 3) Rank spearman analysis results showed that there was a significant relationship between the role of extension to the level of emprowerment of human reseurces and a significant level of productive economic emprowerment but no signifikan effect on the level of institutional emprowerment sago farmers.